Santri Darul Qu’an Al-Karim Banyumas Dalam Kegiatan Produksi Pakchoi Secara Hidroponik - Noor Farid; Slamet Rohadi Suparto; Tridjoko Agustono (JURNAL PRODIKMAS Hasil Pengabdian Kepada Masyarakat, 2018)
The purpose of this agriculture extension was increasing santri’s knowledge concerning with pakchoi hydroponics and santri’s proficiency in the business of Pakchoi hydroponic. The method applied in this community services were counseling and training in Pakchoi hydroponic cultivation as well as mentoring, monitoring and evaluation, packaging and marketing. The results of this project has increased santri’s knowledge and practice ability in the Pakchoi hydroponics and in the entrepreneurship ability. The participation of santri in this activity seemed to be enthusiastic in carrying out activities and all harvested product had been sold out. The entrepreneurship of the given Pakchoi plant has run well and the santri have experience in running the Pakchoi hydroponic business.